Microprocessors and interfacing : - Hall, Douglas V. (McGraw-Hill, 2012)
An Overview of Computers and Microprocessors 2. 8085 and 8086 Microprocessor Architectures 3. 8086 Family Assembly Language Programming—Introduction 4. Implementing Standard Program Structures in 8086 Assembly Language 5. Strings, Procedures, and Macros 6. 8086 Instruction Descriptions and Assembler Directives 7. C, A High-level Language for System Programming 8. Semiconductor Memories and Interfacing 9. Input and Output Modes and Interfacing 10. Digital Interfacing 11. Analog Interfacing and Industrial Control 12. Microcomputer System Peripherals 13. Computer System and Peripheral Buses 14. Data Communication Interfaces 15. The 80286, 80386 and 80486 Microprocessors 16. An Introduction to the Pentium Processors Appendix A ---- Intel manual on 8086 Microprocessor Appendix B ---- 8086/8088 Instructions Appendix C ----- The SDK -86 Appendix D ----- Multimedia Technologies Appendix E -----Lab Assignments